Professional football training strategies during home confinement in the COVID-19 pandemic - Albino, P.; Ponzo, A.; D'Ottavio, S.; Pollara, G.; Ventura, A.; Rodia, F. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: SARS-CoV-2 emergency forced athletes to train at home on their own and mostly unsupervised, making it difficult to provide training solutions. The aims of the study were 1) to collect data and experiences from a Serie A male football team, a top-level female football team and a male young elite football team; 2) to compare data from lockdown and pre-lockdown period; 3) to report changes in training strategies adopted to overcome logistical constraints and 4) to evaluate their congruence to cardio, strength and stretching recommendation mentioned above; 5) to report compliance through player daily feedback. METHODS: Three different professional football teams were enrolled. From March 16, 2020 to April 13, 2020, data for each team were recorded weekly and compared to a standard training period (October 15th to November 15th, 2019) from the same groups. The rate of perceived exertion (RPE), Visual Analogue Scale (VAS) and Total Quality of Recovery Scale (TQR) values were used to compare the two periods using The Student t-Test and Pearson Test. RESULTS: Each group chose a different training approach. Between the pre-lockdown and the lockdown period, there was no significant difference in the VAS, TQR and RPE indexes. Other else players` compliance differed between the groups during the lockdown period. CONCLUSIONS: Most athletes maintained a high level of training during the COVID-19 forced isolation, thanks to the help of team athletic trainers who provide functional tools and indications customized for each differ. Athletes` feedback and compliance differed according to their gender and age. Monitoring with live video sessions and social group sharing among younger players improved compliance and aggregation.